2013
DOI: 10.1021/jf403156c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acid and Alkaline Pretreatments on the Molecular Network of Wheat Gluten and on the Mechanical Properties of Compression-Molded Glassy Wheat Gluten Bioplastics

Abstract: Wheat gluten can be converted into rigid biobased materials by high-temperature compression molding at low moisture contents. During molding, a cross-linked protein network is formed. This study investigated the effect of mixing gluten with acid/alkali in 70% ethanol at ambient temperature for 16 h followed by ethanol removal, freeze-drying, and compression molding at 130 and 150 °C on network formation and on types of cross-links formed. Alkaline pretreatment (0-100 mmol/L sodium hydroxide or 25 mmol/L potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…It appears that large differences in the degree of WG cross-linking prior to moulding do not necessarily have an effect on the flexural properties of moulded products in the case of glassy materials. This finding is in agreement with results by Jansens et al (2013b) who showed that pre-treatment of WG at increasing alkaline concentration lead to significant differences in the protein network with various degrees of LAN formation. However, the properties of moulded articles from these samples showed little dependence on the concentration of the base.…”
Section: Properties Of Compression Moulded Articlessupporting
confidence: 93%
“…It appears that large differences in the degree of WG cross-linking prior to moulding do not necessarily have an effect on the flexural properties of moulded products in the case of glassy materials. This finding is in agreement with results by Jansens et al (2013b) who showed that pre-treatment of WG at increasing alkaline concentration lead to significant differences in the protein network with various degrees of LAN formation. However, the properties of moulded articles from these samples showed little dependence on the concentration of the base.…”
Section: Properties Of Compression Moulded Articlessupporting
confidence: 93%
“…2b and Supplementary Fig. S1a), and with lysine, forming the LAL crosslinks [5,33,34]. Formation of irreversible crosslinks has previously been described in gliadin at alkaline pH and in extruded WG when NH 4 OH and SA were used as additives [35,36].…”
Section: Protein Solubility and Molecular Interactionsmentioning
confidence: 74%
“…Different types of gluten crosslinks are present in rigid, glassy gluten materials, but disulfide bonds are predominant . To improve the strength and failure strain of rigid gluten materials, molecules with multiple terminal thiol (SH) groups can be incorporated into the protein structure .…”
Section: Introductionmentioning
confidence: 99%